2012
DOI: 10.1007/s10456-012-9268-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Semaphorin 4D cooperates with VEGF to promote angiogenesis and tumor progression

Abstract: The semaphorins and plexins comprise a family of cysteine-rich proteins implicated in control of nerve growth and development and regulation of the immune response. Our group and others have found that Semaphorin 4D (SEMA4D) and its receptor, Plexin-B1, play an important role in tumor-induced angiogenesis, with some neoplasms producing SEMA4D in a manner analogous to vascular endothelial growth factor (VEGF) in order to attract Plexin-B1-expressing endothelial cells into the tumor for the purpose of promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 53 publications
1
53
0
Order By: Relevance
“…Studies proved SEMA4D regulate blood vessel growth and endothelial cell homing during vessel development (Carmeliet et al, 2005). Zhou et al examined the contribution of SEMA4D to tumorinduced angiogenesis when compared to VEGF and suggested that targeting these proteins might represent a complementary or parallel mode of treatment for antiangiogenic therapy of HNSCC and other solid tumors exhibiting insensitivity of anti-VEGF therapy (Zhou et al, 2012). Notably, our previous study demonstrated overexpression of SEMA4D was positively correlated with EOC angiogenesis (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Studies proved SEMA4D regulate blood vessel growth and endothelial cell homing during vessel development (Carmeliet et al, 2005). Zhou et al examined the contribution of SEMA4D to tumorinduced angiogenesis when compared to VEGF and suggested that targeting these proteins might represent a complementary or parallel mode of treatment for antiangiogenic therapy of HNSCC and other solid tumors exhibiting insensitivity of anti-VEGF therapy (Zhou et al, 2012). Notably, our previous study demonstrated overexpression of SEMA4D was positively correlated with EOC angiogenesis (Chen et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…225,226 Because sema4D activates angiogenesis using the plexin-B1 receptor and not the VEGFR-2 receptor used by VEGF, it follows that sema4D can act additively with VEGF and that inhibition of sema4D signaling can represent an alternative anti-angiogenic treatment strategy. 227 Sema4D enhances the expression of PDGF-B and angiopoietin like protein-4 in endothelial cells which in turn inhibits the association between pericytes and endothelial cells thereby influencing proliferation and differentiation of pericytes and vascular permeability, whereas VEGF lacks these effects.…”
mentioning
confidence: 99%
“…The role of Sema4D produced by tumor cells in inducing tumor angiogenesis, invasiveness, and progression has been demonstrated in several malignancies, both in human and animal models, and correlates with poor prognosis (32)(33)(34)(35)(36)(37)(38). Sema4D overexpression has been described in a large number of human HNSCC tumor tissue samples and in a panel of primary and metastatic cell lines (32).…”
Section: /Lowmentioning
confidence: 99%